TEACHING WRITING HORTATORY EXPOSITION TEXT THROUGH TASK-BASED LANGUAGE TEACHING (TBLT) - Geraldine, Monitha; Sutapa. Y, Y. Gatot; ., Surmiyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract:The objective of the research was to find out whether teaching writing hortatory exposition text through Task-Based Language Teaching (TBLT) is effective or not. It was also designed to find out how significant the effectiveness of teaching writing hortatory exposition text through the use of TBLT is. The research was carried out at SMAN 2 Pontianak. It was a quasi experimental research. The subjects of the research were the eleventh grade students of XI IPA 2 and XI IPA 4. Data analysis showed that experimental group outperformed control group. It was also found that although there was a difference between the students’ mean score of pre-test and post-test of control group in favor of the traditional approach, this difference was not statistically significant. Therefore, it was concluded that TBLT was more effective in teaching writing hortatory exposition text compared to the traditional approach. Keywords: hortatory exposition text, writing, TBLT Abstrak:Tujuan dari penelitian ini adalah untuk mengetahui apakah pengajaran menulis teks hortatory exposition melalui Pengajaran Bahasa Berbasis Tugas (TBLT) efektif atau tidak. Penelitian ini juga dirancang untuk mengetahui seberapa besar efektivitas pengajaran menulis teks hortatory exposition melalui pendekatan TBLT. Penelitian ini dilakukan di SMA Negeri 2 Pontianak. Metode penelitian yang digunakan adalah quasi experimental. Subyek penelitian adalah siswa kelas XI IPA 2 XI dan XI IPA 4. Analisis data menunjukkan bahwa kelompok eksperimen mengungguli kelompok kontrol.Penelitian ini juga menemukan bahwa meskipun ada perbedaan antara skor rata-rata siswadari pre-test dan post-test dari kelompok kontrol yang mendukung pendekatan tradisional, perbedaan ini tidak signifikan secara statistik. Oleh karena itu, dapat disimpulkan bahwa TBLT lebih efektif dalam pengajaran menulis teks hortatory exposition dibandingkan dengan pendekatan tradisional. Kata kunci: teks hortatory exposition, menulis, TBLT